Development and evaluation of an intervention package to alleviate the psychological effects of premenstrual syndrome in adolescent girls - Hannah Asadi; Hossein Ghamari Kivi; Zahra Akhavi Samarein (BMC Women's Health)
Abstract Objective This study aimed to develop and evaluate the effectiveness of a therapeutic package combining Cognitive Behavioral Therapy (CBT), Narrative Therapy, and a gender-sensitive approach to reduce the psychological and emotional challenges of Premenstrual Syndrome (PMS) in adolescent girls. Methodology Using a quasi-experimental design, 30 adolescent girls from Saqqez, Iran, were randomly assigned to an intervention group (n = 15) or a control group (n = 15). The intervention group participated in a researcher-developed group therapy program over 10 sessions, focusing on reducing rumination and pain-related catastrophic thinking. Assessments were conducted pre-test, post-test, and at follow-up using validated psychological scales. Data were analyzed using ANCOVA. Results The intervention significantly reduced rumination and pain catastrophizing in the experimental group compared to the control group (p < 0.05). These effects were sustained at follow-up, indicating the intervention's lasting impact on improving cognitive and emotional regulation. Conclusion The findings demonstrate that a therapeutic package integrating CBT, Narrative Therapy, and cultural sensitivity can effectively alleviate PMS-related psychological symptoms in adolescent girls. This approach holds promise for broader applications in educational and counseling settings to enhance adolescent well-being.